LINC00346 Sponges miR-30c-2-3p to Promote the Development of Lung Adenocarcinoma by Targeting MYBL2 and Regulating CELL CYCLE Signaling Pathway - Xu, Qian; Xu, Zhenwu; Zhu, Kai; Lin, Jinlan; Ye, Bo (Frontiers in Oncology, 2021)
Background: LINC00346 has recently been reported to regulate the development of several cancer types, but its biological functions and underlying mechanisms in lung adenocarcinoma (LUAD) have not been elucidated. The purpose of this study was to investigate the molecular mechanism of LINC00346 in the progression of LUAD. Methods: Bioinformatics was performed to find the target lncRNA, miRNA and mRNA, and the binding relationship between the target genes was verified by dual luciferase reporter gene and RIP assays. Fluorescence in situ hybridization was used to detect the location of LINC00346 in LUAD tissues. The expressions of LINC00346, miR-30c-2-3p and MYBL2 in each group were detected by qRT-PCR, and western blot was performed to detect expressions of MYBL2 and CELL CYCLE related proteins. Proliferation, metastasis, apoptosis and cell cycle of LUAD cells were detected by CCK-8, colony formation, Transwell and flow cytometry assays, respectively. Mouse xenograft models were established to further determine the effects of LINC00346 on LUAD tumor growth in vivo. Results: LINC00346 was upregulated in LUAD tissues and cells and was mainly localized in the cytoplasm. Knockdown of LINC00346 inhibited tumor growth in vivo, proliferation, metastasis and cell cycle progression, while induced apoptosis. LINC00346 sponged miR-30c-2-3 by targeting MYBL2 and regulating CELL CYCLE signaling pathway. Inhibiting miR-30c-2-3p or overexpressing MYBL2 could reverse the inhibitory effect of LINC00346 knockdown on LUAD process. Conclusions: LINC00346 as a ceRNA played a carcinogenic role in the development of LUAD via miR-30c-2-3p/MYBL2 axis regulating the CELL CYCLE signaling pathway. The study generally elucidated the mechanism by which LINC00346 regulated the development of LUAD, providing new ideas for the diagnosis and treatment of LUAD guided by lncRNA.